ANALISIS PENGARUH KEPUASAN KERJA, KEADILAN PROSEDURAL DAN KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA CV. SURYA NUSANTARA SAFETY MEDAN - Simbolon, Sahat (Sekolah Tinggi Manajemen Bisnis (STMB) MultiSmart, 2021)
This study aims to describe the effect of job satisfaction, procedural justice and compensation on employee work productivity at CV. Surya Nusantara Safety Medan. This research was conducted for 4 (four) months, start from May 2019 until August 2019. This research use non probability sampling method. The respondents of this research are all employee at CV. Surya Nusantara Safety Medan which amounted to 82 (eighty two) employee. The instrument is used a questionnaire to collent data from job satisfaction variable, procedural justice variable, compensation variable and employee work productivity variable. Data analysis technique used is validity test, reliability test, descriptive analysis, multicolinearity test, normality test, multiple linear regression analysis, multiple linear correlation coefficient test, partial hypothesis test ot t test, simultaneous hypothesis test or F test, and calculation of coefficient of determination. The result of descriptive analysis for job satisfaction variable, procedural justice variable, compensation variable and employee work productivity are in good category at CV. Surya Nusantara Safety Medan. Based on partial analysis, job satisfaction, procedural justice and compensation have a positive and significant effect on employee work productivity at CV. Surya Nusantara Safety Medan. Simultaneously, job satisfaction, procedural justice, compensation have a positive and significant influence on employee work productivity at CV. Surya Nusantara Safety Medan. The contribution of job satisfaction, procedural justice and compensation variable to improve the employee work productivity variable is 0,803 or 80,3 %, while rest of 0,197 or 19,7 % influenced by other variable not examined by writer in this research, such as work environment, work ethic, leadership, experience/ years of service, concern, and another else.